Pengaruh Pelaksanaan Layanan Informasi Terhadap Pengenalan Lingkungan Belajar Siswa Di Mal Uin-Su Medan - Nursyahfitri Simangunsong (Proceedings of Annual Conference on Islamic Educational Management, 2021)
Guidance and counseling on the introduction of the learning environment that occurs in students of MAL UIN North Sumatra Medan. The information service provided is to introduce and convey a number of information needed by students, especially those relating to the introduction of the learning environment so that students can participate in learning activities as well as possible. The subjects of this study were students of MAL UIN North Sumatra TP 2016/2017, the total number of which consisted of class X, XI and XII, the total was 308 students. Meanwhile, as a sample, one class was taken, namely X.2 as many as 48 people. The data collection instrument used in addition to observations, interviews and document studies used a questionnaire regarding the implementation of information services (30 questions) and the introduction of the learning environment (32 questions), while the data analysis technique used specifically regarding the correlation between the implementation of information services and the introduction of the learning environment was Product Moment correlation technique. After analyzing and calculating the correlation between information services and the student learning environment, rxy = 0.648, the level of this relationship is included in the category of moderate relationship level interval. To find out whether the correlation between the information service variable and the student learning environment variable is accepted or not, the rcount value is compared with the rtable value. The rtable value for n=48 and the significance level of = 5% is 0.284. The value of rcount > rtable value or 0.648 > 0.284, it can be concluded that information services have a significant relationship with the learning environment of MAL UIN North Sumatra students. So from the results of the calculation of the coefficients above, it can be seen that 41.96% of the student learning environment of MAL UIN North Sumatra is influenced by information services and the remaining 58.04% is a factor from outside this research.